(untitled) (Research, Society and Development, 2023)
Sudden Infant Death Syndrome (SIDS) is defined by its unexplained and multifactorial origin. Its clinical presentation is that when a baby is placed on a surface after ingesting liquids, after an interval of time, they are found dead, lying in the same position in which they were previously placed. Thus, SIDS is considered one of the main causes of infant mortality in babies under 12 months of age. The aim of this study is to address the epidemiology, pathophysiology, signs and symptoms and diagnosis of Sudden Infant Death Syndrome, in order to provide study material and support for health professionals. Methodology: This study is an integrative literature review which, after selecting articles from the Scielo and Pubmed databases, filtered articles in Portuguese, Italian, Spanish and English published between 2018 and 2023. Results: 130 articles were identified and, firstly, 60 articles were excluded after reading the title. After this stage, the abstracts were read and 39 articles were excluded. In the end, another 10 were excluded after a thorough reading, and 21 articles were selected and used to write this article. Conclusions: The study shows the importance of training health professionals so that they can provide guidance, promote prevention and reduce the incidence of SIDS.